Adapting cities to sea level rise : green and gray strategies - Al, Stefan; Westerhof, Edgar (Washington : Island Press, 2018)
Adapting Cities to Sea Level Rise, by infrastructure expert Stefan Al, introduces design responses to sea-level rise, drawing from examples around the globe. Going against standard engineering solutions, Al argues for approaches that are integrated with the public realm, nature-based, and sensitive to local conditions and the community. He features design responses to building resilience that creates new civic assets for cities. For the first time, the possible infrastructure solutions are brought together in a clear and easy-to-read format. The first part of the book looks at the challenges for cities that have historically faced sea-level rise and flooding issues, and their response in resiliency through urban design. He presents diverse case studies from New Orleans to Ho Chi Minh to Rotterdam, and draws best practices and urban design typologies for the second part of the book. Part two is a graphic catalogue of best-practices or resilience strategies. These strategies are organized into four categories: hard protect, soft protect, store, and retreat. The benefits and challenges of each strategy are outlined and highlighted by a case study showing where that strategy has been applied.
Keywords: URBANISMO -- ASPECTOS AMBIENTALES; ARQUITECTURA -- ASPECTOS AMBIENTALES; NIVEL DEL MAR -- FACTORES CLIMÁTICOS; LLANURAS ALUVIALES -- ASPECTOS AMBIENTALES; ARQUITECTURA COSTERA; ARQUITECTURA SOSTENIBLE